Seasonal Differences in Plankton Community and Removal Efficiency of Nutrients and Organic Matter in a Subtropical Constructed Wetland - Travaini-Lima, Fernanda [UNESP]; Milstein, Ana; SipaÃºba-Tavares, LÃºcia Helena [UNESP] (Springer Nature, 2016)
The performance of free water surface flow constructed wetlands (CW) may be impaired by abiotic factors. The effects of seasons on the water quality improvement and on the community of plankton were evaluated in a CW system with the macrophytes Cyperus giganteus Vahl, Typha domingensis Pers., Eichhornia crassipes (Mart.) Solms and Pontederia cordata L. Water, plankton and macrophytes were sampled in the inflow and outflow during the dry and rainy seasons. Differences in temperature, precipitation, hydraulic loading rate (HLR), hydraulic retention time (HRT), inlet mass loadings and plant biomass between seasons affected the treatment efficiency. High precipitation and the consequent increase in HLR along with an increase in temperature and lower macrophyte biomass, were correlated to lower rates of removal efficiency during the rainy season. The season with higher macrophytes abundance coincided with high retention of zooplankton and solids. Higher nutrient levels in the dry season corresponded with a dominance and abundance of r-strategist planktonic species. To increase the removal efficiency of nutrients and organic matter by CW systems, care should be taken to decrease the HLR especially in periods of high precipitation.
Keywords: Annual cycles; Biological treatment; Phytoplankton; Species diversity; Species richness; Zooplankton